An Update on Drug-induced Oral Reactions - Hila Yousefi; Mohammas Abdollahi (Frontiers Media S.A., 2018)
Adverse drug reactions (ADRs) are one of the major culprits in the development of oral lesions, which can be misdiagnosed with underlying diseases. The goal of this study is to summarize and update the current knowledge about drug-induced oral reactions. Electronic searches were performed in Scopus, Google Scholar, Cochrane and PubMed databases, for articles published between January 2008 and August 2017. Two authors screened the titles and abstracts for eligibility. Finally, 56 studies included in this review. There was no systematic homogeneity in the included studies; thereby no meta-analysis was performed. The most frequent oral ADR was xerostomia,andthe most reported cause was antihypertensive medications. Cardiovascular drugs were the most reported culprit agents for induction of oral ulcerative and vesiculo-bullous lesions, followed by methotrexate. Nonsteroidal anti-inflammatory drugs (NSAIDs) and β-blockers were found the most common responsible drugs for induction of oral lichen planus.   This article is open to POST-PUBLICATION REVIEW. Registered readers (see "For Readers") may comment by clicking on ABSTRACT on the issue's contents page.